Systematic characterization of gene families and functional analysis of PvRAS3 and PvRAS4 involved in rosmarinic acid biosynthesis in Prunella vulgaris - Yan, Chao; Li, Caili; Jiang, Maochang; Xu, Yayun; Zhang, Sixuan; Hu, Xiangling; Chen, Yuhang; Lu, Shanfa (Frontiers in Plant Science, 2024)
Prunella vulgaris is an important material for Chinese medicines with rosmarinic acid (RA) as its index component. Based on the chromosome-level genome assembly we obtained recently, 51 RA biosynthesis-related genes were identified. Sequence feature, gene expression pattern and phylogenetic relationship analyses showed that 17 of them could be involved in RA biosynthesis. In vitro enzymatic assay showed that PvRAS3 catalyzed the condensation of p-coumaroyl-CoA and caffeoyl-CoA with pHPL and DHPL. Its affinity toward p-coumaroyl-CoA was higher than caffeoyl-CoA. PvRAS4 catalyzed the condensation of p-coumaroyl-CoA with pHPL and DHPL. Its affinity toward p-coumaroyl-CoA was lower than PvRAS3. UPLC and LC-MS/MS analyses showed the existence of RA, 4-coumaroyl-3’,4’-dihydroxyphenyllactic acid, 4-coumaroyl-4’-hydroxyphenyllactic acid and caffeoyl-4’-hydroxyphenyllactic acid in P. vulgaris. Generation and analysis of pvras3 homozygous mutants showed significant decrease of RA, 4-coumaroyl-3’,4’-dihydroxyphenyllactic acid, 4-coumaroyl-4’-hydroxyphenyllactic acid and caffeoyl-4’-hydroxyphenyllactic acid and significant increase of DHPL and pHPL. It suggests that PvRAS3 is the main enzyme catalyzing the condensation of acyl donors and acceptors during RA biosynthesis. The role of PvRAS4 appears minor. The results provide significant information for quality control of P. vulgaris medicinal materials.